Bedensel engelli sporcuların toplumsal hayata katılımında sporun etkisi - Özay, Fatma Hüma (My University, 2019)
Amaç:Bu çalışmada bedensel engelli sporcuların toplumsal hayata katılımında sporun etkisinin araştırılması hedeflenmiştir.Gereç ve Yöntem: Çalışmanın araştırma grubu Pendik Ampute Futbol Takımı, Tuzla Belediyesi Spor Kulübü, İstanbul Özürlüler Spor Kulübü, Beşiktaş Spor Kulübü’ndeki bedensel engelli 18 yaş üstü 32 sporcudur. Araştırmada derinlemesine görüşmelerden faydalanılarak yarı yapılandırılmış görüşme tekniğiyle, sporcuların hayatında spor öncesi ve spor sonrası iş, aile, arkadaşlık ve toplumsal hayata katılım düzeylerindeki değişimler konu edinilmiştir.Bulgular: Profesyonel engelli sporunun, gündelik yaşam faaliyetlerine katılmada, kişilerin beklenen toplumsal rollerini gerçekleştirmede, bireyin toplumsal hayatına katılımında ve toplumsal kimlik yaratımında olumlu kazanımlar sağladığına dair katılımcı yaklaşımları gözlemlenmiştir.

Purpose: This study has been established by practically investigating the effects of sports on social integration of athletes with physically disability in today’s Turkey.Materials and Methods: The research group of the study is 32 athletes over 18 years old with physical disability who joined our study voluntarily. The athletes are part of Pendik Ampute Football Team, Tuzla Municipality Sports Club, Istanbul Disability Sports Club and Beşiktaş Sports Club. In this study, the main issues disccussed include the changes observed in work, family, friendship and social life of athletes who attempted participating in professional sports activities. In doing this, in-depth interviews and semi-structured interview techniques are used. Conclusion: Approaches of athletes with physical disabilities who accepted to join our study have been observed that; professional disabled sports provide positive gains on athletes’ participation in daily activities, fitting in the expected social roles of the individual and facilitation of individual’s identity acquisition in social life.
Keywords: Athletes; Bedensel Engellilik; Disability Sport; Engelli Bireylerin Toplumsal Hayata Katılımı Social Integration; Engelli Sporu; Engelliler; Niteliksel Araştırma; Öğrenim ve öğretim; People with disabilities; Physical Disability; Qualitative Research; Social Integration of Athletes with Physical Disability; Spor; Sporcular; Sports; Study and teaching; Toplumsal Hayata Katılım